KAJIAN SIFAT MEKANIK BATANG BAMBU DENGAN ISIAN MORTAR PADA DESAIN GEOMETRI SAMBUNGAN - Astuti Masdar; Mhd. Ryan Angryanof; Muhammad Idris; Umar Khatab; Ronny Jnnnaidy; Muhammad Yazid (Racic : Rab Construction Research, 2026)
Bamboo has become a preferred construction material to replace wood because it has superior mechanical strength and is environmentally friendly. One of the superior bamboo species is petung bamboo (Dendrocalamus asper). Petung bamboo is known for its large stem size and high strength, making it potentially used as a structural material. However, the hollow and fibrous shape of bamboo makes it prone to breaking, especially when stress concentration occurs with a small contact area at the joint. Bamboo stems can break due to uneven shrinkage and expansion. In this condition, filling is carried out in the stem cavity of the bamboo connection system, one of which is by filling with mortar. This study aims to determine the effect of the presence of mortar as a filling in the bamboo stem on the mechanical properties related to the analysis of bolt spacing in the intact bamboo connection system including shear strength and bearing strength as well as determining the value of the physical properties of bamboo in the form of water content and density. The study was conducted experimentally referring to the ISO 22157–2019 standard. The test specimens consisted of Petung bamboo with and without mortar filling as a comparison. It is hoped that the results of this study will reveal the extent to which the use of mortar as a filling in bamboo stems can improve the shear resistance and bearing strength of bamboo stems, thereby providing additional references for the design of intact bamboo joints that use mortar filling in the stems.